DISTRIBUTION AND FREQUENCY OF DENTOALVEOLAR FRACTURE OF ANTERIOR TEETH AND ITS MANAGEMENT IN PAEDIATRIC PATIENTS - Eida Vitria, Evy; Setya Putri Cahyani , Rheinata (Fakultas Kedokteran Gigi Unjani, 2025)
Dentoalveolar fractures are the most common types of orofacial fractures. Differences influence variations in prevalence across regions in fracture classification systems, demographic factors, and the behaviors that lead to trauma. This study aimed to determine the distribution and frequency of anterior dentoalveolar fractures based on age, gender, cause of fracture, classification of fracture, and its management. At Dental and Oral Hospital Faculty of Dentistry, Universitas Indonesia, from October 2019 to October 2024. A retrospective descriptive approach took secondary data from paediatric patients at the Dental and Oral Hospital, Faculty of Dentistry, University of Indonesia, from October 2019 to October 2024. In a study of 113 fracture cases, 68.1% were dentoalveolar fractures, with 29.2% meeting inclusion criteria involving 48 teeth. The highest incidence occurred in the 10–18-year age group (45.5%), predominantly in males (57.6%). Falls were the leading cause (66.7%), and uncomplicated crown fractures were most common (45.8%). Primary tooth fractures (Class IX) were the most frequently found (39.6%) and most commonly occurred in the upper first incisors (75%). Composite restorations were the most common treatment (39.6%). This study demonstrates that dentoalveolar fractures in paediatric patients predominantly affect male adolescents, with falls being the leading cause, and permanent teeth, especially the maxillary central incisors, being the most impacted. Composite restoration is the most commonly performed treatment method. DOI : 10.54052/jhds.v5n1.p31-42